Peer Mentoring Circles in higher education: perceptions of their members with and without disability and program proposal - Maia, Marisa; Santos, Paula; Espe-Sherwind, Marilyn (Frontiers in Education, 2024)
The increase of the number of students with disabilities in Higher Education, including students with intellectual disability, emphasizes the need for Higher Education Institutions to provide support for their inclusion and learning. Within inclusive Higher Education peers can have a fundamental role through Peer Mentoring Circles. This qualitative study aims to understand the perceived experiences of members of Peer Mentoring Circles, within the scope of a program that provided academic support, during an academic semester, to mentees with intellectual disability. Data collection included semi-structured interviews with members of the Circles (two mentees and seven mentors), and the facilitator's field notes. Content analysis was used to analyze the data. Through the data analysis, two categories were identified: components of the Peer Mentoring Circles program and experiences of the members of the Circles. The data generated suggest that both mentors and mentees had positive experiences, contributing to the development of the mentees' skills. The data generated suggests that the experiences lived by the mentors and mentees were positive and its contributions to the development of the mentees' skills. Based on literature and the data generated emerged the proposal for the Peer Mentoring Circles program with a broad set of guidelines for its implementation, which can set the baseline for developing future peer mentoring programs in Higher Education aimed not only at students with disabilities, but also at other students with support needs such as international students.